Sustainable energy management – the importence of the renewable energy sources, their difficulties and chances - Dombi, Mihály (Acta Agraria Debreceniensis, 2009)
The biggest question of the century standing before us is that if people will be able to direct the development to sustainable direction. One of the components of global problems threatening us is the pressure that the energy management puts on the environment, which can be significantly lowered by utilizing renewable energy sources. The aim of my study is to draft the model of a sustainable energy management, putting the renewable energy sources into it in a sensible way, regarding the possibilities of Hungary.